2017
DOI: 10.1111/cyt.12489
|View full text |Cite
|
Sign up to set email alerts
|

Rosettes in papillary carcinoma of thyroid: A rare cytomorphological indicator of aggressive variants

Abstract: We present a case of tall cell variant of papillary carcinoma of thyroid diagnosed on cytology showing predominance of rosette‐like formations. Also described previously for the columnar cell variant, these rosettes need to be differentiated from micro‐follicles and are an indicator for aggressive variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 6 publications
3
11
0
Order By: Relevance
“…In our case, we also observed branching tubule‐like structures, a striking admixture of normal thyroid follicular cells and thick colloid in the background, and many spindle cells forming rosettes with central basement membrane‐like material, also depicted in the cytology microphotographs of a published case of SETTLE . These structures probably represent tumour cells from areas of stromal hyalinisation, and have also been described in SS, and in tall cell/columnar cell/cribriform‐morular variants of papillary thyroid carcinoma . Cytological diagnosis of SETTLE requires a high index of suspicion, and immuno cyto chemistry and/or molecular testing would be necessary to exclude mimics.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our case, we also observed branching tubule‐like structures, a striking admixture of normal thyroid follicular cells and thick colloid in the background, and many spindle cells forming rosettes with central basement membrane‐like material, also depicted in the cytology microphotographs of a published case of SETTLE . These structures probably represent tumour cells from areas of stromal hyalinisation, and have also been described in SS, and in tall cell/columnar cell/cribriform‐morular variants of papillary thyroid carcinoma . Cytological diagnosis of SETTLE requires a high index of suspicion, and immuno cyto chemistry and/or molecular testing would be necessary to exclude mimics.…”
Section: Discussionsupporting
confidence: 75%
“…11 These structures probably represent tumour cells from areas of stromal hyalinisation, and have also been described in SS, 12 and in tall cell/ columnar cell/cribriform-morular variants of papillary thyroid carcinoma. 13,14 Cytological diagnosis of SETTLE requires a high index of suspicion, and immunocytochemistry and/or molecular testing would be necessary to exclude mimics.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a few papers have described the presence of a rosette-like component representing a minor or focal feature in cytological samples from both benign and malignant thyroid lesions, even though they lacked pictures demonstrating this pattern. [11][12][13][14][15][16][17] In our series of 150 BL we did not find any true rosette or pseudorosette follicular structures, confirming that this pattern is likely linked more with malignant thyroid nodules. The case report by Sen et al is, to the best of our knowledge, the only paper reporting the presence of rosettes in a thyroid FNAC with CCV-PTC, which triggered the reason to undertake our study.…”
Section: Discussionsupporting
confidence: 71%
“…However, rosettes have been previously documented in cytological samples from benign and malignant lesions such as adenomatous goiter, insular carcinoma and medullary thyroid carcinoma). [11][12][13][14][15][16][17] Sen et al also reported the presence of a rosette-like pattern in a fine needle aspiration cytology (FNAC) specimen of a well-differentiated thyroid follicular carcinoma diagnosed as columnar cell variant (CCV) of papillary thyroid carcinoma (PTC). 12 Only a few other papers have reported this finding associated with thyroid carcinoma in which a rosette-like pattern was linked with aggressive variants of PTC including the tall cell variant (TCV) of PTC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation